Differences in the stratum corneum of Indonesian infants and adults - Tsutomu Fujimura; Kyoko Shima; Yuki Miyauchi; Mitsuyuki Hotta; Hiroshi Hashimoto; Danang Agung Yunaidi; Ratih Sofia Ika Putri; Puspita Ningrum; Yoshinori Takema (Paediatrica Indonesiana, 2017)
Background Although understanding the stratum corneum (SC) of infant skin is important to avoid skin diseases such as atopic dermatitis, there has been no such investigation in Indonesian infants to date.Objective Â To obtain a basic knowledge of SC characteristics in Indonesian infants in order to develop methods for infant-specific skin care and to prevent dermatitis and infection.Methods Seventy-two healthy, full term infants aged 1 to 24 months who were native Indonesians residing in Jakarta were enrolled in this study. Some of the mothers were also enrolled in the study as adults (n=30). Transepidermal water loss (TEWL) and hydration of the SC (capacitance) on the thigh, buttock, and upper arm were measured after sufficient acclimation in an air-conditioned room, in both infants and mothers. Results The SC hydration was significantly higher in infants than adults at all sites measured, including the buttocks, which is a diaper area. Infant TEWL values were also significantly higher than in adults at all sites. Hydration of the SC and TEWL values showed no significant correlation with age of infant for any site. The SC hydration and TEWL values of Indonesian infants did not decrease to adult values within 24 months, which indicates that the SC characteristics in infants continue to develop after 24 months of age.Conclusion Â Indonesian infants aged 0-24 months have significantly higher SC hydration and TEWL values than Indonesian mothers. However, infant age has no correlation to SC hydration or to TEWL values.